Experimental investigation of effects of airflows on plasma-assisted combustion actuator characteristics - 刘兴建 何立明 于锦禄 张华磊 (Chinese physics B, 2015)
The effects of the airflow on plasma-assisted combustion actuator （PACA） characteristics are studied in detail. The plasma is characterized electrically, as well as optically with a spectrometer. Our results show that the airflow has an obvious influence on the PACA characteristics. The breakdown voltage and vibrational temperature decrease, while the discharge power increases compared with the stationary airflow. The memory effect of metastable state species and the transportation characteristics of charged particles in microdischarge channel are the dominant causes for the variations of the breakdown voltage and discharge power, respectively, and the vibrational temperature calculated in this work can describe the electron energy of the dielectric barrier discharge plasma in PACA. These results offer new perspectives for the use of PACA in plasma-assisted combustion.